2023
DOI: 10.3390/admsci13030072
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Accounting Factors through Audited Financial Statements in Businesses toward a Circular Economy: Why a Sustainable Profit through Qualified Staff and Investment in Technology?

Abstract: This study examines the investigation of accounting factors through audited financial statements in businesses by analyzing the qualified staff and investment in technology for sustainable profit. Therefore, the main goal is to analyze whether qualified staff and investment in technology affect the sustainability of profit in businesses through the investigation of accounting factors in the audited financial statements toward a circular economy, more specifically in these financial items: total assets (TASS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 113 publications
1
4
0
Order By: Relevance
“…This study was started by identifying the kind of CAATs utilized by internal auditors in the companies' internal audit functions. The outcome revealed that information technology is not intensively used in the internal audit processes, corresponding to other studies' findings (Pedrosa et al, 2020;Lulaj et al, 2023;Bernards et al, 2022;Alex et al, 2022). Internal auditors know they can use technology better and admit its adoption has challenges (Cachón-Rodrí guez et al, 2021).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study was started by identifying the kind of CAATs utilized by internal auditors in the companies' internal audit functions. The outcome revealed that information technology is not intensively used in the internal audit processes, corresponding to other studies' findings (Pedrosa et al, 2020;Lulaj et al, 2023;Bernards et al, 2022;Alex et al, 2022). Internal auditors know they can use technology better and admit its adoption has challenges (Cachón-Rodrí guez et al, 2021).…”
Section: Discussionsupporting
confidence: 76%
“…Accounting transparency is critical for most companies, and accounting ethics is related to corporate sustainability. According to J. E. Margret and Peck (2014), corporate social responsibility matters are gradually vital to firms and sustainable business operations (Lulaj et al, 2023) because of the consequences of fraud. Bernards et al (2022) demonstrate that the current demands for advanced technologies spread the link between organizational operations (corporate governance) and audit culture.…”
Section: Value Creation For Shareholdersmentioning
confidence: 99%
“…Regarding the factor (F5) or the applications offered by the business to make payments during the purchase of the product/service according to Martinez and Mc Andrews (2022), it is emphasized that there is still reluctance on the part of consumers to make payments via the Internet related to products/services. According to Lulaj et al (2023), it was emphasized that to have a sustainable profit, businesses must be careful in total liabilities, increase the performance of total assets, increase the performance of net income and total business income, as well as provide training for increasing the skills of workers and improving technology (equipment, machinery, etc.). It is therefore recommended that businesses bring something else through (TIS) to have sustainability of profit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investment in qualified staff and technology affects the sustainability of profit in businesses [75]. The cost of transporting goods from a producer in one country to a final destination is vital for profitability analysis.…”
Section: Potential Profitabilitymentioning
confidence: 99%